Preservice Teachers’ Commitment in Teaching Profession - Purnama, Syahrul (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
National reports from numerous nations found a significant percentage of teacher education graduates do not enter teacher profession (OECD 2005). According to Manuel & Hughes (2006), The expectations of preservice teachers for their future work environment are crucial to investigate because they provide insight into the motivation that drives future endeavors The goal of this study was to analyze preservice teachers' career decisions based on different levels of commitment to teaching. It has identified the commitment types of preservice teachers based on their reason for pursuing a career as a teacher, as well as their perspectives of the professional and external conditions. The motivational desire to make a decision regarding pursuing and preparing for the teaching profession is defined as committed to the teaching profession. The writer found whether “perennial problem” happened since preservice teachers through their commitment, motivation, and perspective about teaching profession. This is descriptive research that attempts to qualitative research. The total of participants are 42 preservice teachers who study in the Faculty of Teaching Education Program, in Cirebon. this research discovered that different types of preservice teachers have distinctive motives and perspectives of the teaching profession. The findings of this study revealed that various combinations of factors were important to each preservice teacher group's decision to enter teaching profession as a career, but that common sources of impact were discovered for all four groups of participants. Furthermore, these findings have important implications for educational programs and policymakers in presenting teaching as a worthwhile profession that is essential to society's advancement.